Grammatikalisierung als Glied in der Kette der Sprachwandelprozesse anhand von ausgewählten Beispielen aus der ostdeutschen ‚‚Apostelgeschichte‘‘ aus dem 14. Jahrhundert - Piotr A. Owsiński (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
The article hereunder presents the language analysis of the “Acts of the Apostles” from 14th century published by Walther Ziesemer in 1927. The text of an unknown scribe was written in Early New High German in the Silesian dialect. The aim of the paper is to analyze the grammaticalization’s grade of chosen morphological and syntactic language features. In the investigation there is scrutinized the using of the mandatory subject pronouns and of the articles, which can be seen as a result of the weakening of vowel articulation and the subsequent development of the vowels in the unstressed syllables. The third part of the paper concerns the forming of the German future tense (Futur I) and its absolute presence in the analyzed text from the middle of the 14th century without other forms with the modal or motion verbs. The author introduces the results of his analysis showing the stage of the development of the chosen morphological and syntactic phenomena with the appropriate examples.